Effect of Astaxanthin on Cycling Time Trial Performance - Earnest, C.P.; Lupo, M.; White, K.M.; Church, T.S. (International Journal of Sports Medicine, 2011)
We examined the effect of Astaxanthin (AST) on substrate metabolism and cycling time trial (TT) performance by randomly assigning 21 competitive cyclists to 28d of encapsulated AST (4 mg/d) or placebo (PLA) supplementation. Testing included a VO2max test and on a separate day a 2 h constant intensity pre-exhaustion ride, after a 10 h fast, at 5% below VO2max stimulated onset of 4 mmol/L lactic acid followed 5 min later by a 20 km TT. Analysis included ANOVA and post-hoc testing. Data are Mean (SD) and (95% CI) when expressed as change (pre vs. post). Fourteen participants successfully completed the trial. Overall, we observed significant improvements in 20 km TT performance in the AST group (n=7; −121 s; 95%CI, −185, −53), but not the PLA (n=7; −19 s; 95%CI, −84, 45). The AST group was significantly different vs. PLA (P<0.05). The AST group significantly increased power output (20 W; 95%CI, 1, 38), while the PLA group did not (1.6 W; 95%CI, −17, 20). The mechanism of action for these improvements remains unclear, as we observed no treatment effects for carbohydrate and fat oxidation, or blood indices indicative of fuel mobilization. While AST significantly improved TT performance the mechanism of action explaining this effect remains obscure.
Keywords: cycling; nutrition; ergogenic aid; performance; supplement